Dynamics of market shaping and its consequences - Hacklin, Leena (My University, 2021)
Market shaping refers to planned proactive actions, which aim to modify a market. Market shaping phenomenon has been studied, however more research is needed to widen the understanding of this ample phenomenon. Previous research specifically emphasizes the need of longitudinal case studies focusing on the consequences of market shaping. Hence, longitudinal research focusing on the consequences of market shaping was chosen as the theme of this study. This research combines results from several peer-reviewed articles to form a visual three-dimensional market shaping framework. According to the defined framework market shaping consists of shapers, actions, objects, targets, and consequences. All of the mentioned market shaping elements are interlinked and have a dynamic, versatile nature. Additionally, both external and internal events affect the market shaping process. The empirical part of this research focuses on the changes in Finnish electricity production during years 2010-2020. Governmental action, namely passing The Act on Production Subsidy for Electricity Produced from Renewable Energy is defined as a market shaping event. This event consists of shapers, actions, objects, targets, and consequences. The key interest of the empirical part of this research is to find evidence that supports and further develops existing market shaping theory. Versatile empirical data on electricity production provided information about the changes in the electricity market and increased the knowledge of the market shaping phenomenon. Specifically, this research provides results about expressions describing market shaping consequences. The nature of the consequences is identified and categorized based on the information gathered from previous research and evidence from this research. Orderliness, effect, significance, anticipation, immediacy, permanence, typicality, and linearity describe market shaping consequences. Additionally, this research identifies several future research topics, and the need to deepen the understanding of market shaping phenomenon is apparent. Successful market shaping provides powerful opportunities for all market participants. Hence, this subject is important for both researchers and market participants.

Markkinoiden muokkaaminen on suunnitelmallista ja proaktiivista toimintaa, jolla tavoitellaan markkinoiden muutosta. Markkinoiden muokkaamista on laaja-alaisesti tieteellisten menetelmien avulla tutkittu ja useita vertaisarvioituja julkaisuja aiheeseen liittyen on saatavilla. Tutkimustulokset kuitenkin korostavat, että lisätutkimusta tarvitaan, jotta tietämys tähän laaja-alaiseen ilmiöön liittyen kasvaa. Erityisesti on korostettu tarvetta pitkittäistutkimukselle, joka keskittyy markkinoiden muokkaamisprosessin seurauksiin. Tämä tutkimus yhdistää ja tiivistää tutkimustuloksia useista eri tieteellisistä lähteistä. Työssä esitetään visuaalinen kolmiulotteinen markkinoiden muokkaamisen viitekehys. Määritellyn viitekehityksen mukaan markkinoiden muokkaaminen koostuu muokkaajista, toimista, kohteista, tavoitteista ja seurauksista. Markkinoiden muokkaaminen on dynaaminen ja monitahoinen ilmiö, jossa osatekijät vaikuttavat toinen toisiinsa. Lisäksi markkinoiden muokkaamistapahtumaan vaikuttavat sekä prosessin sisäiset että ulkoiset tapahtumat ja tekijät. Työn empiirisessä osuudessa tarkastellaan Suomen sähkömarkkinan muutoksia vuosien 2010–2020 aikana. Markkinoiden muokkaamistapahtumana on eduskunnan päätöksen mukaisesti säädetty laki uusiutuvilla energialähteillä tuotetun sähkön tuotantotuesta ja sen vaikutukset sähkömarkkinaan. Monipuolisen ja laajan tutkimusaineiston avulla havainnollistetaan markkinoiden muokkaamistapahtuman vaikutuksia markkinaan. Tutkimuksessa kiinnitetään erityisesti huomiota seuraamuksia kuvailevien sanojen tunnistamiseen. Suunnitelmallisuus, vaikutus, merkittävyys, ennakoitavuus, välittömyys, pysyvyys, tyypillisyys ja lineaarisuus kuvaavat mahdollisia markkinoiden muokkaamisen seurauksia. Lisäksi tutkimuksen perusteella tunnistetaan useita potentiaalisia jatkotutkimusaiheita. Markkinoiden muokkaaminen on monipuolinen ja laaja ilmiö, joten lisätutkimusta tarvitaan tietämyksen kasvattamiseksi. Onnistunut markkinoiden muokkaamisprosessi on tehokas tapa muokata markkinaa suunnitelmallisesti. Tämän ilmiön ymmärtäminen on tärkeää sekä alan tutkijoille että markkinatoimijoille.
Keywords: market shaping, electricity market